Binding Transnational Lesbian‑Feminist Print Constellations: Exploring Feminist Print Cultures and Its Transnational Travels - Enszer, Julie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
A series of publishing interventions by lesbian-feminists document the transnational aspirations of the U.S. women’s liberation movement in the 1970s, 80, and 90s. The argument about how lesbian‑feminist publishers contributed to transnational feminist attentions unfolds in three parts. First, I examine how feminists built international publishing networks in the 1980s and 1990s. Second, I examine how three lesbian-feminist periodicals, Connexions, Sinister Wisdom, and Ikon, demonstrated commitments to transnational publishing and reading practices. Third, a constellation of five transnational texts published by independent lesbian-feminist publishers reveal the literacies imagined by feminist publishers and how lesbian‑feminist publishers worked to reshape American feminist imaginaries to be more transnational. In a final section, I speculate about how focusing on lesbian‑feminist publishing in the past might illuminate contemporary studies of publishing and inspire new publishing activists.